Conrad in the public eye : biography, criticism, publicity - Peters, John G. (John Gerard) (Conrad studies, 2008)
This is a collection of difficult-to-find and typically early commentary on Conrad's life and works. The selections contained shed light on Conrad's life and works, as well as the way in which his works were promoted to the public. Selections include those by the American novelist Christopher Morley and the Irish novelist Liam O'Flaherty. Also included is a previously unpublished essay by Conrad's friend Richard Curle. Of particular interest are the promotional materials, which are collected together for the first time and reveal how Conrad was perceived by the general reading public and how he was marketed by his publishers.